Strategic synergies and perspectives of their evaluation in the process of strategic analysis - Błaszczyk, Marek (Strategiczne synergie i perspektywy ich oceny w procesie analizy strategicznej, 2018)
Although the subject of synergy has been explored for a long time, there are many indications that it is still gaining in importance, in the field of economics. The phenomenon of synergy seems particularly important in the field of M&A’s, alliances and the development of new organizational forms of enterprises. Synergy effects are most often evaluated from the operational and very rarely in the strategic, structural perspectives. The aim of the article is to identify and systematize the most important perspectives for synergy effect evaluation in the process of strategic analysis. The identified perspectives will be the starting point of the further research on criteria selection for synergy effects evaluation and will be one of the components of a more complex framework of the process of resource analysis. The research was conceptual, based on a literature review in the fields of methodology of strategic analysis, strategic management and Resource-Based View (RBV) approach. The identification of the structural conditions for synergy effect evaluation, requires focusing on: the subjective scope of the synergy effect analysis, key areas of strategy content and context, with the important role of strategic resources
Management Sciences = Nauki o Zarządzaniu, 2018, vol. 23, no. 4; s. 9-17
Keywords: strategy; synergy; strategic analysis; resources; core competencies